HARMONIZATION OF COMMERCIAL TRANSACTION LAW IN THE ASEAN REGION: THE IMPORTANCE, POSSIBILITIES AND CHALLENGES - Jovanka Lingkanaya (Law Review, 2021)
The Southeast Asian region is viewed as a united block that is ASEAN. The ASEAN roots from a diverse economic system, culture, ethnic, technical, and educational system. In the modern-day globalization, economic globalization continues to develop as well. This economic globalization pushes the importance of having an integrated commercial transaction law of the ASEAN member states. The idea of integration that stems from a rapidly growing economic globalization results in an unavoidable demand for harmonization of commercial transaction law within the ASEAN region. As a united region that is the ASEAN, having different regulations to govern matters of cross border commercial transactions inter-ASEAN would hinder the effectiveness of each country’s law itself. Yet, the importance of having a harmonized commercial transaction law within the ASEAN region is still questioned. This paper will analyze on the importance of having a harmonized commercial law among the ASEAN member states, the possibility and challenges of developing such a harmonization and if possible, how the ASEAN Economic Community (AEC) is planning to develop a form of harmonization in its commercial transaction law.